2013
DOI: 10.4161/hv.24832
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and safety of three 2010–2011 seasonal trivalent influenza vaccines in Chinese toddlers, children and older adults

Abstract: The 2009 influenza A(H1N1) pandemic strain was for the first time included in the 2010-2011 seasonal trivalent influenza vaccine (TIV). We conducted a double-blind, randomized trial in Chinese population to assess the immunogenicity and safety of the 2010-2011 TIV manufactured by GlaxoSmithKline and compared it with the counterpart vaccines manufactured by Sanofi Pasteur and Sinovac Biotech. Healthy toddlers (6-36 mo), children (6-12 y) and older adults (≥60 y) with 300 participants in each age group were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…No serious or life-threatening AE was reported. This result is similar to that of a clinical trial conducted in China in 2013, 11 which demonstrated that all 3 TIVs were well tolerated. However, we observed a higher incidence of systemic reactions with the imported influenza vaccine (GSK TIV) than with the 2 domestic vaccine (Sinovac TIV and Pasteur TIV).…”
Section: Resultssupporting
confidence: 88%
“…No serious or life-threatening AE was reported. This result is similar to that of a clinical trial conducted in China in 2013, 11 which demonstrated that all 3 TIVs were well tolerated. However, we observed a higher incidence of systemic reactions with the imported influenza vaccine (GSK TIV) than with the 2 domestic vaccine (Sinovac TIV and Pasteur TIV).…”
Section: Resultssupporting
confidence: 88%
“…31 In the 2010/2011 season, obvious immune response was observed in both children and the elderly. 32 The seroprotection rates against H1N1 and H3N2 were more than 70% in children and more than 60% in the elderly, and the seroconversion rates against the 2 strains were all more than 30%. The seroprotection rate against B antigen was more than 30% in both children and the elderly and the seroconversion rates was more than 20%.…”
Section: Rapid Immune Responsementioning
confidence: 93%
“…Clinical data in this review on Anflu ® comes from pre-market licensure trial, 21 annual trials sponsored by Sinovac Biotech [22][23][24][25][26][27][28][29][30][31] (Table 1) and investigator-initiated clinical trials. [32][33][34]…”
Section: Anflu®: a Preservative-free Unadjuvanted Split-virus Tivmentioning
confidence: 99%
See 1 more Smart Citation
“…Literally the split-vaccines are "the happy medium" in influenza prophylaxis because the level of their side effects is similar to that of subunit vaccines and their immunological effectiveness is analogous to the same of whole-virus vaccines. [5][6][7] Influenza vaccine production capacity all over the world is 350 million doses per year. In case of pandemic the world vaccine manufacturing companies will fail to meet the global demand.…”
mentioning
confidence: 99%